SUBSTITUSI SARI BAYAM MERAH PADA PEMBUATAN KERUPUK NASI (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2022)
This research was motivated by the absence of a community or cracker industry that processes crackers made from natural additives, such as the addition of red spinach juice to rice crackers. This is evidenced that there are still many crackers made from artificial additives to produce good color, taste and texture. The purpose of this study was to see how the quality of rice crackers with the addition of mareh spinach juice in terms of aroma, color, taste and texture. The research method used is the experimental method. Data collection techniques used are literature studies and questionnaires. This research was assessed by expert panelists, namely the Bunda Tourism Academy lecturer, while the general panelists were the surrounding community. The results of experimental research using organoleptic tests showed that rice crackers with 50% red spinach juice substitution had aroma qualities, namely red spinach flavor, red color, red spinach taste very strong, very crunchy texture. Rice crackers with a substitution of 70% purple sweet potato have a very strong aroma of red spinach, a very red color, a very strong taste of red spinach, and a crunchy texture.